Strategic Management of the HW Scouting Program to Develop the National Character of Elementary School Students - Untung, Slamet; Martaningsih, Sri Tutur; Suyatno, Suyatno (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
National character plays a vital role in the educational process as it serves as the foundation for shaping students' attitudes, values, and behaviors, which must be implemented through school activities, including Hizbul Wathan scouting. This study aims to describe the implementation of strategic management within the Hizbul Wathan (HW) scouting program to strengthen the national character of elementary school students at SD Muhammadiyah Komplek Kolombo. This research employed a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews, and documentation studies, with research subjects selected through purposive sampling. Data analysis followed the interactive model—comprising data reduction, data display, and verification of findings—utilizing triangulation techniques and ATLAS.ti software to ensure data validity. The results indicate that the management of the HW program, based on POAC functions (planning, organizing, actuating, and controlling), is executed structurally through the formulation of annual programs, the formation of activity groups, the implementation of routine training integrated into intracurricular activities, and program evaluation via activity monitoring and student progress reporting. The implementation of these strategies contributes to the development of discipline, responsibility, cooperation, leadership, and a sense of patriotism among students. Consequently, the Hizbul Wathan scouting program serves as a strategic medium for strengthening national character education in elementary schools.